Mucins as contrast agent targets for fluorescence-guided surgery of pancreatic cancer. (1st May 2023) - Muilenburg, Kathryn M.; Isder, Carly C.; Radhakrishnan, Prakash; Batra, Surinder K.; Ly, Quan P.; Carlson, Mark A.; Bouvet, Michael; Hollingsworth, Michael A.; Mohs, Aaron M.
Abstract: Pancreatic cancer is difficult to resect due to its unique challenges, often leading to incomplete tumor resections. Fluorescence-guided surgery (FGS), also known as intraoperative molecular imaging and optical surgical navigation, is an intraoperative tool that can aid surgeons in complete tumor resection through an increased ability to detect the tumor. To target the tumor, FGS contrast agents rely on biomarkers aberrantly expressed in malignant tissue compared to normal tissue. These biomarkers allow clinicians to identify the tumor and its stage before surgical resection and provide a contrast agent target for intraoperative imaging. Mucins, a family of glycoproteins, are upregulated in malignant tissue compared to normal tissue. Therefore, these proteins may serve as biomarkers for surgical resection. Intraoperative imaging of mucin expression in pancreatic cancer can potentially increase the number of complete resections. While some mucins have been studied for FGS, the potential ability to function as a biomarker target extends to the entire mucin family. Therefore, mucins are attractive proteins to investigate more broadly as FGS biomarkers. This review summarizes the biomarker traits of mucins and their potential use in FGS for pancreatic cancer. Graphical abstract: Image 1 Highlights: Mucins can be differentially or uniquely expressed in pancreatic cancer allowing them to serve as contrast agent targets. Fluorescently-labeled, mucin-targeting molecules, e.g. antibodies, can intraoperatively illuminate pancreatic cancer. Intraoperative imaging, or fluorescence-guided surgery, can potentially increase the rate of complete tumor resection. Mucin-targeting fluorophores are in preclinical development and could complement other surgical imaging agents.